EFFECT OF FERMENTED Sauropus androgynus LEAVES ON BLOOD LIPID FRACTION AND HAEMATOLOGICAL PROFILE IN BROILER CHICKENS - Santoso, U.; Fenita, Y.; Kususiyah, K. (Diponegoro University, 2015)
This study was conducted to evaluate effect of fermented Sauropus androgynus leaves on blood lipid fractions and haematological profiles in broilers. One hundred and twelve broilers were distributed to 7 treatment groups. One group was fed diets without Sauropus androgynus leaves as the control, and other six groups were fed Sauropus androgynus leaves fermented by Neurospora crassa, Lactobacillus sp. or Saccharomyces cerevisiae at level of 25 g or 50 g/kg diet. Experimental results showed that the treatments had no effect on cholesterol, high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c) and atherogenic index, very low-density lipoprotein cholesterol (VLDL-c) and triglyceride concentration (P>0.05). It was shown that fermented Sauropus androgynus leaves significantly affected red blood count (RBC), white blood count (WBC), packed cell volume (PCV), trombosit dan erythrocyte sedimentation rate (ESR) (P